2016
DOI: 10.1002/ece3.2294
|View full text |Cite
|
Sign up to set email alerts
|

Extensive variation, but not local adaptation in an Australian alpine daisy

Abstract: Alpine plants often occupy diverse habitats within a similar elevation range, but most research on local adaptation in these plants has focused on elevation gradients. In testing for habitat‐related local adaptation, local effects on seed quality and initial plant growth should be considered in designs that encompass multiple populations and habitats. We tested for local adaptation across alpine habitats in a morphologically variable daisy species, Brachyscome decipiens, in the Bogong High Plains in Victoria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The most rigorous method of testing for local adaptation is reciprocal transplant experiments (Blanquart, Kaltz, Nuismer, & Gandon, 2013). Most knowledge on local adaptation comes from such studies of individual species (e.g., Bischoff & Trémulot, 2011;Mendola, Baer, Johnson, & Maricle, 2015;Mathiasen & Premoli, 2016;Evans et al, 2016;Hirst, Sexton, & Hoffmann, 2016;Lu, Parker, Colombo, Man, & Baeten, 2016 and many others). While a classical reciprocal transplant experiment involves at least two origins of a single species transplanted reciprocally to both sites of origin, some studies simplified this design to only multiple origins in one site (Gellie, Breed, Thurgate, Kennedy, & Lowe, 2016;Hancock, Leishman, & Hughes, 2013), whereas others have extended it to multiple origins of multiple species in multiple sites (e.g., Bischoff et al, 2006;Bucharova et al, 2017;Carter & Blair, 2012;Joshi et al, 2001;Körner et al, 2016;Kramer, Larkin, & Fant, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most rigorous method of testing for local adaptation is reciprocal transplant experiments (Blanquart, Kaltz, Nuismer, & Gandon, 2013). Most knowledge on local adaptation comes from such studies of individual species (e.g., Bischoff & Trémulot, 2011;Mendola, Baer, Johnson, & Maricle, 2015;Mathiasen & Premoli, 2016;Evans et al, 2016;Hirst, Sexton, & Hoffmann, 2016;Lu, Parker, Colombo, Man, & Baeten, 2016 and many others). While a classical reciprocal transplant experiment involves at least two origins of a single species transplanted reciprocally to both sites of origin, some studies simplified this design to only multiple origins in one site (Gellie, Breed, Thurgate, Kennedy, & Lowe, 2016;Hancock, Leishman, & Hughes, 2013), whereas others have extended it to multiple origins of multiple species in multiple sites (e.g., Bischoff et al, 2006;Bucharova et al, 2017;Carter & Blair, 2012;Joshi et al, 2001;Körner et al, 2016;Kramer, Larkin, & Fant, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Third, the "sympatric vs. allopatric" approach (unfortunately sometimes called "home vs. away" in older studies) uses multiple local populations and compares the general performance of plants growing in their local environments (sympatric) with plants growing outside their local environments (allopatric). Only the last approach allows to detect general patterns in local adaptation as it is not site-specific (Blanquart et al, 2013), as exemplified by Joshi et al (2001), Bischoff et al (2006), Hirst et al (2016. The analysis approach depends on the experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…While it is possible that local adaptation may take more time than allowed in our experiment to express depending on plant longevity (Bennington et al 2012;Hirst et al 2016), the most likely explanation for the lack of local adaptation in our study is related to the narrow habitat niche of G. reptans. This species grows at high elevation, typically in glacier forelands, close to the glacier snout, and in moist scree fields (Aeschimann et al 2004).…”
Section: Little Evidence For Local Adaptationmentioning
confidence: 79%
“…An alternative, not mutually exclusive, explanation for the lack of local adaptation in our study could be that highly plastic phenotypic responses to local environmental conditions may overcome the need for genetic differentiation among populations, especially in perennial herbs (Antonovics and Primack 1982;Bazzaz 1996;Cheplick 2015;Hirst et al 2016). Indeed, our study revealed that G. reptans had a great capacity to respond plastically to environmental conditions (Tables 2, 3), which can represent a means to maximize plant performance in heterogeneous environments (Alpert and Simms 2002;Stöcklin et al 2009;Nicotra et al 2010).…”
Section: Little Evidence For Local Adaptationmentioning
confidence: 83%
See 1 more Smart Citation